Academic Freedom in a Plural World (Central European University Press, 2025)
The notion of academic freedom dates back to the creation of universities and has long been understood to be central to their vocation. This freedom has come under attack by different actors throughout its history. In the current context, rising threats to democracy and human liberties, the corporatization of research, concerns about diversity and increased societal polarization, are putting a considerable pressure on its exercise. However, academic freedom is also a concept that suffers from persistent ambiguities associated with the general notion of freedom as well as debates about the function of universities.This edited collection addresses the question of academic freedom by situating it in its broader global context. More conceptual treatments contribute to an understanding of academic freedom as distinct and separate from, although related to, freedom of expression, or student rights. These conceptual treatments are combined with studies of actual struggles over the scope of academic freedom in specific universities. The contributions come from a broad variety of sites seek to deprovincialize the conversation beyond North America or the English-speaking world.